Exosomes derived from alcohol-treated hepatocytes horizontally transfer liver specific miRNA-122 and sensitize monocytes to LPS - Momen-Heravi, Fatemeh (Sci Rep, 2015)
Hepatocyte damage and inflammation in monocytes/macrophages are central to the pathogenesis of alcoholic hepatitis (AH). MicroRNAs (miRNAs) regulate all of these processes. MiRNA-122 is abundantly expressed in hepatocytes while monocytes/macrophages have low levels. The role of exosomes in AH and possible cross talk between hepatocyte-derived exosomes and immune cells is not explored yet. Here, we show that the number of exosomes significantly increases in the sera of healthy individuals after alcohol binge drinking and in mice after binge or chronic alcohol consumption. Exosomes isolated from sera after alcohol consumption or from in vitro ethanol-treated hepatocytes contained miRNA-122. Exosomes derived from ethanol-treated Huh7.5 cells were taken up by the recipients THP1 monocytes and horizontally transferred a mature form of liver-specific miRNA-122. In vivo, liver mononuclear cells and Kupffer cells from alcohol-fed mice had increased miRNA-122 levels. In monocytes, miRNA-122 transferred via exosomes inhibited the HO-1 pathway and sensitized to LPS stimulation and increased levels of pro-inflammatory cytokines. Finally, inflammatory effects of exosomes from ethanol-treated hepatocytes were prevented by using RNA interference via exosome-mediated delivery of a miRNA-122 inhibitor. These results demonstrate that first, exosomes mediate communication between hepatocytes and monocytes/macrophages and second, hepatocyte-derived miRNA-122 can reprogram monocytes inducing sensitization to LPS.